2018
DOI: 10.1111/jph.12775
|View full text |Cite
|
Sign up to set email alerts
|

The potential of antagonistic moroccan Streptomyces isolates for the biological control of damping‐off disease of pea (Pisum sativum L.) caused by Aphanomyces euteiches

Abstract: Three hundred and fifty‐nine isolates of actinobacteria collected from different Moroccan soils were evaluated for their in vitro antimicrobial activity against the oomycete pathogen Aphanomyces euteiches, the causal agent of damping‐off of pea and other legumes. Eighty‐seven isolates (24%) had an inhibitory in vitro effect against A. euteiches. Fourteen bioactive isolates with the greatest inhibitory effect against A. euteiches and no inhibitory effect on plant beneficial rhizobia were tested for their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…From the unexplored hot Merzouga desert, one hundred and sixty-three Actinobacteria isolates were obtained, of which 59% showed a high biological diversity with the greatest growth inhibition of pathogens tested [ 21 ]. The study reported by Oubaha et al shows that Streptomyces species isolated from rhizospheric soils displayed a potent inhibitory effect against Aphanomyces euteiches causing the damping‐off disease of pea ( Pisum sativum L.) [ 60 ]. However, Actinobacteria from Moroccan mining habitats have not been investigated for their biocontrol potential.…”
Section: Discussionmentioning
confidence: 99%
“…From the unexplored hot Merzouga desert, one hundred and sixty-three Actinobacteria isolates were obtained, of which 59% showed a high biological diversity with the greatest growth inhibition of pathogens tested [ 21 ]. The study reported by Oubaha et al shows that Streptomyces species isolated from rhizospheric soils displayed a potent inhibitory effect against Aphanomyces euteiches causing the damping‐off disease of pea ( Pisum sativum L.) [ 60 ]. However, Actinobacteria from Moroccan mining habitats have not been investigated for their biocontrol potential.…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetes are Gram+ bacteria that represent a high proportion of the soil microbial biomass and have the ability to produce a wide variety of antibiotics and of extracellular enzymes. Several strains of actinomycetes have been found to control plant diseases [59][60][61]. Recently, [62] were identifed β-rubromycin as a P. infestans cyst germination inhibitor by screening compounds produced by Streptomyces isolated from soil.…”
Section: Actinomycetesmentioning
confidence: 99%
“…Biological interactions between plants and endophytic microorganisms may cause reduced amounts of biological stressors. In fact, metabolic studies have shown that endophytic microorganisms play a role in strengthening and growing plants by stimulating the production of plant hormones such as auxins and gibberellins, or as plant protection agents against microbial pathogens and insects (Ek‐Ramos et al, 2019 ; Oubaha et al, 2019 ). In a research conducted in 2014, it was observed that the overexpression of malic acid‐producing genes in the endophytic bacterial strains increased the release of phosphate in the soil, and as a result led to higher number of lateral branches with higher length of the stem and roots in wheat plants (Jog et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%